Investigation of In-vivoantidiarrhoeal and insecticidal activity of Trewianudijlora leaf extract - Duyti, Sayeza Yeara (BRAC Univeristy, 2017)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016.